Evolutionary Games, Complex Adaptive Systems and Hayek’s Austrian Perspective:: A Preliminary Discussion - Tellez-Zepeda, Claudio A. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
The Austrian School of Economics and Evolutionary Economics are two apparently incompatible heterodox approaches. The purpose of this paper is to advance an initial step towards the development of an approach that is both evolutionary and Austrian. I contend that one of the barriers to such an approach is the fact that F. A. Hayek resorted to group selection in his evolutionary interpretation of the markets and society. I argue that it is possible to develop an evolutionary Austrian perspective by interpreting evolutionary games as complex adaptive systems, abandoning the idea of group selection and introducing a proper selection unit.